A Ilustracao (Paris, 1884-1892) e a Revista de Portugal (Porto, 1889-1892): dialogues between editorial projects and technical possibilities - Luca, Tania Regina de [UNESP] (Univ Federal Rio De Janeiro, 2017)
The aim of this article is to investigate the origins and characteristics of the first project concerning the Revista de Portugal, carried out by Eca de Queiroz. The periodical was launched in 1889 and played a major role in the aesthetic and political issues of its time. However, little is known about the circumstances influencing the decision to create the periodical, the comings and goings of its editorial conceptions, the intentions that were not accomplished, and the role of the magazine A Ilustracao, and its director Mariano Pina, as the point of departure for the venture. The analysis of this real case is important because it shows the multiple possibilities offered by the publishing market, which was already effectively internationalized. It also highlights the impact of technical issues on the definition of a periodical's nature as well as the double character of the product, at once merchandise and instrument for public intervention.
Keywords: Ilustracao; Revista de Portugal; Mariano Pina; Eca de Queiroz; Publishing in the nineteenth century